Survei Kondisi Kebugaran Kardiorespirasi Klub Sepakbola Organ Salamrejo - Adittya Puji Pamungkas; Bimo Alexander; Andri Arif Kustiawan; Agus Pribadi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Excellent cardiorespiratory fitness is a fundamental requirement for soccer players to maintain tactical performance throughout a match. This study aimed to analyze the maximum aerobic capacity VO2 Max of players from the Organ Salamrejo Soccer Club, Kulon Progo, which recently suffered league degradation due to physical fatigue. This study employed a descriptive quantitative research design with a survey method. Sampling was conducted using a purposive sampling technique, resulting in 26 senior players as participants. The VO2 Max capacity was measured using a field-based instrument, the Multistage Fitness Test (MFT), on a 20-meter track, and the collected data were analyzed using descriptive statistics. The results revealed that the team's average cardiorespiratory capacity fell into the low category, with a mean score of 37.14 ml/kg/min. Individually, 42% of the players were in the "poor" category, 38% in the "fair" category, 11% in the "good" category, and 9% in the "excellent" category. Positional analysis showed that strikers achieved the highest average VO2 Max (39.75 ml/kg/min), followed by midfielders (39.02 ml/kg/min), wingers (37.76 ml/kg/min), fullbacks (36.10 ml/kg/min), centerbacks (34.96 ml/kg/min), and goalkeepers (33.40 ml/kg/min). In conclusion, the majority of the players did not meet the minimum fitness standards for soccer. Therefore, the coaching staff is highly recommended to overhaul the physical training program by implementing interval or circuit training methods.